Increasing Learning Independence in Elementary School Students through Innovative Learning Models : Literature Study - Romadona, Wina; Atmaja, Hamdan Tri; Sumartiningsih, Sri; Yuwono, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
Conditions in the field show that the level of student learning in elementary school is still relatively low. This condition is caused by the conventional learning model that does not provide opportunities for students to explore, as a result of which students become accustomed to relying on teachers who hinder their independent development. This study aims to examine whether innovative learning models can significantly increase the learning independence of elementary school students. The method used in this study is a literature study. This approach is carried out by browsing various literature related to student learning independence using innovative learning models. The results of the literature review show that various innovative learning models such as Project Based Learning (PjBL), Problem Based Learning (PBL), Discovey Learning, Flipped Classroom, Self Organized Learning Environments (SOLE), technology-based learning models and IT Media such as Augmented Reality, Numbered Heads Together, game-based learning models such as LEGO and Mission X, inquiry and problem-based learning models, roleplay models and RADEC models are consistently effective in increasing student learning independence at various levels of education, especially in elementary schools.